Oral lichen planus and its recent management: A review - Md Ashif Iqbal; Suraiya Yesmin; Fathimath Maaisha; Shaama Ibrahim; Puja Gotame (Update Dental College, 2020)
Background: Oral Lichen Planus (OLP) is one of the most common dermatological disease which is present in the oral cavity. It is a chronic autoimmune, mucocutaneous disease that affects oral mucosa as well as the skin, genital mucosa and other sites of the body.Method: In this review study, various databases such as Google Scholar, PubMed Central, Hinari and Cochrane library were searched for articles with keywords lichen planus, oral lichen planus, premalignant lesions, management of Lichen planus. Articles were searched from January 2015 to 5th November 2020.Result: From the 34 articles obtained after reviewing the abstracts, most relevant 32articles were evaluated in this study.Conclusion: The etiology, pathophysiology, clinical presentation, histopathological features, diagnosis and various management for oral lichen planus is discussed. This article also compares the existing and the most recent treatment modalities that are available throughout the world that are discussed in the literatures. However, more intensive studies must be carried out to find the best treatments which are cost-effective in the long run. Update Dent. Coll. j: 2020; 10 (2): 29-34